Dawabit al-Takfir ‘Inda Ibn Taymiyyah - Nofriyanto Nofriyanto (Universitas Darussalam Gontor, 2017)
This article discusses the concept of takfir according to Ibn Taymiyyah. In the conception of takfir, he stated that takfir is part of sharia laws which has its own rules and guidelines. The rules and guidelines regarding this takfir, are uncomprimizing terms that should be fulfilled as well as the absence of the resistence. Thus there are two terms; first, is the intention; Secondly, the arrival of proof and strong evidence whereby the perpetrator that can not be unreasonable to do so because of ignorance. In addition, according to Ibn Taymiyyah, the takfir issues must be distinguished between individual takfir and general takfir. Individual takfir, leads to legal consequences that private individuals who’s accused by being kafir considered to have apostated from Islam. Instead, the general takfir is not so.